(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This study aims to analyze policy capacity in the implementation of women and children’s protection programs in Southwest Papua Province. The study used a qualitative approach with a case study design. The theory used is the Policy Capacity Framework by Xun Wu, Howlett, and Ramesh (2017), which covers three dimensions: analytical capacity, operational capacity, and political capacity. The results show that support for program implementation is in place, but its effectiveness remains limited. In terms of analytical capacity, the utilization of the SIMFONI-PPPA system and SAPA 129 services has shown progress, but is still hampered by limited infrastructure, human resources, and the absence of a technical institution such as the UPTD-PPA. Data collection and analysis processes are still manual, thus not supporting evidence-based policymaking. In terms of operational capacity, the implementation of service SOPs, outreach, training, and the provision of safe houses has been ongoing, but is still partial and not institutionally coordinated. Meanwhile, in terms of political capacity, there is government commitment and community support, but protection policies have not been a top priority due to the lack of Regional Regulations (Perda) and strong institutional legitimacy. This study recommends strengthening policy capacity through integrated data systems, establishing a UPTD-PPA (Regional Women’s Empowerment and Child Protection Unit), improving cross-sectoral coordination, adding professional staff and supporting facilities, and ratifying the Regional Regulation on the Protection of Women and Children. These efforts are expected to strengthen the effectiveness, sustainability, and inclusiveness of the PPA program in Southwest Papua Province.